Congenital Pulmonary Malformation in Children - Montasser Nadeem; Basil Elnazir; Peter Greally (Scientifica, 2012)
Congenital Pulmonary Malformations (CPMs) are a group of rare lung abnormalities affecting the airways, parenchyma, and vasculature. They represent a spectrum of abnormal development rather than discrete pathological entities. They are caused by aberrant embryological lung development which occurs at different stages of intrauterine life.